Zinc supplementation has no effect on circulating levels of peripheral blood leucocytes and lymphocyte subsets in healthy adult men - Bonham, Maxine; O'Connor, Jacqueline M.; Alexander, H. Denis; Coulter, James; Walsh, Paula M.; McAnena, Liadhan B.; Downes, C. Stephen; Hannigan, Bernadette M.; Strain, J. J. (British journal of nutrition, 2003)
As a result of evidence documenting harmful effects of Zn supplementation on immune function and Cu status, thirty-eight men were recruited onto a Zn supplementation trial. The aim was to examine the effects of chronic Zn supplementation on circulating levels of peripheral blood leucocytes and lymphocyte subsets. Subjects (n 19) took 30 mg Zn/d for 14 weeks followed by 3 mg Cu/d for 8 weeks to counteract adverse effects, if any, of Zn supplementation on immune status resulting from lowered Cu status. A control group (n 19) took placebo supplements for the duration of the trial. Dietary intakes of Zn approximated 10 mg/d. Blood samples, taken throughout the trial, were assessed for full blood profiles and flow cytometric analyses of lymphocyte subsets. Putative indices of Cu status were also examined. Results indicate that there was no effect of Zn supplementation on circulating levels of peripheral blood leucocytes or on lymphocyte subsets. Cu status was also unaltered. Independent of supplement, there appeared to be seasonal variations in selected lymphocyte subsets in both placebo and supplemented groups. Alterations in circulating levels of B cells (cluster of differentiation (CD) 19), memory T cells (CD45RO) and expression of the intracellular adhesion molecule-1 (CD54) on T cells were observed. Findings indicated no adverse effects of Zn supplementation on immune status or Cu status and support the US upper level of Zn tolerance of 40 mg/d. The seasonal variations observed in lymphocyte subsets in the group as a whole could have implications for seasonal variability in the incidence of infectious diseases.